How to satisfy consumer expectations for mandarin? A cross-cultural study in Spain and Italy - Giménez-Sanchís, Adrián; Farina, Vittorio; Tarancón, Paula; Besada, Cristina (2024)
Determining consumer quality requirements is needed to provide markets with high quality fruit, which helps to reduce fruit waste both at home and at points of sale. This cross-cultural study investigated how important are different mandarin attributes in the repurchase intention of Spanish and Italian consumers. Four-hundred and fifty consumers from each country participated in an on-line survey where they scored mandarin attributes according to their importance. Cluster analysis revealed that in both countries consumers can be divided into two groups: “Consumers focused on mouth perceptions” and “Multisensory consumers”. Among Spanish participants, 41% belonged to the first group and 59% to the second one, while in Italy 52% of consumers belonged to the first group and 48% to the second. “Consumers focused on mouth perceptions” reported that the most important attributes that mandarins should have to buy them again are: ‘sweet’, ‘balance sweet-acid’, ‘intense flavour’, ‘juicy’ and ‘not fibrous’. For this group of consumers, other attributes that are mainly perceived with the hands and sight (easy peeling, not messy when eating, pulp colour) and ‘seedless’ were not important aspects. “Multisensory consumers” stated that all the attributes mentioned above that are related to taste and texture perceived in mouth are very important. Moreover, they reported that characteristics like easy peeling, seedless or pulp colour are also relevant. The less important attribute for both groups of consumers was ‘not messy when eating’. In addition to the percentage of participants in each cluster, the main differences among Italian and Spanish consumers were that in general Italian consumers gave more importance to ‘aromatic’ and ‘pulp colour’ attributes and less importance to ‘not fibrous’ than the Spanish ones